Elimination of Criminal Sanctions in a Forced Defense that Transgresses Limits as a Form of Justice - Heni Susanti; Mutia Meduri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The aim of the article is to prove that not all criminal acts can be punished. There is a rule that states if someone commits a crime for reasons of compulsion that exceeds the limit, it cannot be punished. The urgency of this research is that justice must be upheld, therefore criminals who commit crimes for reasons of Noodweer Excesses must be protected and given the opportunity for their rights as citizens to get justice in accordance with existing rules.. This research is a type of normative legal research. Normative research is a process to find the rule of law, legal principles, and legal doctrines to answer the legal issues faced. The form of justice can be seen in the fulfillment of the elements of Article 49 Paragraph 2 of the Criminal Code regarding forced defense that exceeds the limit: the existence of a great mental shock due to attacks carried out by witnesses, causing the forced defense transgresses the limit. The act of defense is balanced with the attack that is threatened. Severe mental agitation is not only limited to asthenische affecten as in the form of anxiety, fear, or helplessness, but is a sthenische affecten such as anger, wrath or irritation and the consequences of turning self-defense into an attack and excessive or at least using drastical or disproportionate efforts. There is a threat of attack and an ongoing attack or danger is still threatening.